SELEKSI BAKTERI TERMOFILIK SELULOLITIK PASCA ERUPSI MERAPI - Anna Rakhmawati; Evy Yulianti; Eli Rohaeti (Kaunia: Integration and Interconnection Islam and Science, 2014)
Thermophilic bacteria after the eruption of Merapi in 2010 have been isolated from the Gendol Atas river with dilution and enrichment methods. The purpose of this study was to conduct the selection of these bacteria as producers of cellulase enzymes. Selection was done by growing 348 bacterial isolates on selective media Mandels-CMC 0.5% using Carboxy Methyl Cellulose (CMC) as carbon source. Incubation was performed at 55 °C for 24 hours. The results showed 255 isolates (73.27%) were able to grow in Mandels medium-CMC 0.5%. Bacterial isolates were isolated by enrichment method (69.8%) were more able to grow on selective media compared with the dilution method (30.2%). The diameter of the three largest colonies were isolates D13a (2.44 cm); E135 (2.33 cm); and D110a (1.98 cm).